Video capsule endoscopy and the hidden gastrointestinal diseases - Helmy Ahmed (The Saudi Journal of Gastroenterology, 2006)
Video capsule endoscopy (VCE) has recently been introduced to fill the gap between examinations of the upper and lower gastrointestinal tract, mainly to examine the small bowel (SB) for sources of obscure bleeding in addition to many other indications. VCE represents a minute endoscope, embedded in a swallowable capsule that is propelled by peristalsis and achieves the journey to the right colon in 5-8 hours. Images captured by the capsule are recorded on a hard drive attached to the patient′s belt. Many studies have recently shown that the diagnostic yield of VCE is superior to that of push enteroscopy. This mini-review contains information on the technical aspects, indications, safety and tolerance of VCE. It is well known that radiological investigations of the small bowel (SB) have a limited diagnostic yield, are relatively invasive, and often lead to late discovery of diseases, especially malignancy and profuse bleeding, at a worse stage. Also, push enteroscopy is limited by the depth of the insertion of the instrument to the proximal jejunum and, in the retrograde, to the last 50-80 cm of the terminal ileum, with an ability to visualize the entire SB only in 10-70% of cases. Introduction of video capsule endoscopy (VCE) is therefore regarded a significant advance in investigating intestinal diseases, and closes the gap in evaluating the SB, "the black box" of endoscopy(1). This mini-review describes the current indications of VCE and the prerequisites for accurate examination, and briefly discusses its tolerance and safety.